Answer:
Option C
Explanation:
The complete question is in the attachment.
The given equation is
![2 {x}^(2) - 9x + 2 = - 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tu4m41hu3hxxf63v5r46m5fu98eh7n2xqs.png)
We rewrite in standard form to get;
![2 {x}^(2) - 9x + 3 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pj8yuu4fg0p6fr38r5eqb6ukaiax6h76lo.png)
Compare to
![a {x}^(2) + bx + c = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ah8o2lq88k5wu5zfb26kwa7k7d52env2ye.png)
we have a=2, b=-9 and c=3.
We substitute into the formula for the discriminant:
![D= {b}^(2) - 4ac](https://img.qammunity.org/2021/formulas/mathematics/middle-school/f02qvlqj9c3soeh1ioj7rgymn8csyk98nb.png)
We substitute to get:
![D= {( - 9)}^(2) - 4 * 2 * 3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1dur3ftdjrzxi5sn5p7b70obdftvvn11a9.png)
![D=81- 24 = 57](https://img.qammunity.org/2021/formulas/mathematics/middle-school/592rxl9quwm2f8dwdni6onl3mfi7063mif.png)
Since the discriminant is greater than zero, there are two real roots.